‘SENSORIAL LITTER’: BUILDING REFLEXIVE TRUST THROUGH EXAMINING DIGITAL DETRITUS - Hare, Kathleen Allyson (AoIR Selected Papers of Internet Research, 2019)
How to reflexively examine the ways in which the researcher’s own embodied experiences shape knowledge production is a key question within digital and sensory ethnography. Challenges exist around capturing these embodied experiences through conventional reflexive methods, such as voice and field notes. Furthermore, it can be particularly difficult to capture that which is experienced by the researcher as being ‘too intense’ and resultingly shed or refuse/d by the body; (e.g., fleeting, whirling anxious thoughts; spatial suspensions of disorientation; and voids from pushing away difficult feelings). Nevertheless, as examining refuse/d experiences can focus reflexive engagement on the difficult aspects of fieldwork, this methodological area provides a unique niche for inquiry. In this work, I advance knowledge on retaining and reflecting upon too intense experiences. I first draw from phenomenological embodiment theories to put forward the concept of ‘sensorial litter’. I posit that when shed from the body, intense experiences are not lost, but rather manifest materially through digital media as litter (e.g., anxiety filled texts, emails to supervisors, search histories). Retrieving and examining three pieces of sensorial litter from my own ethnographic work, I then demonstrate how this digital detritus may add critical depth to reflexive engagement with embodiment. Specifically, I illustrate how sensorial litter can provide concrete entry points into the ways in which the researcher’s sensing body is perpetually in flux, shaping and re-shaping throughout fieldwork. I argue that sensorial litter can facilitate reflexive engagement that is many-sited, intertextual, resistant to holism, and perceptive ethnographic research’s inevitable shortcomings.